Behavioral flexibility of the trawling long-legged bat, Macrophyllum macrophyllum (Phyllostomidae) - Weinbeer, Moritz; Kalko, Elisabeth K.; Jung, Kirsten (Frontiers in Physiology, 2013)
We assessed the behavioral flexibility of the trawling long-legged bat, Macrophyllum macrophyllum (Phyllostomidae) in flight cage experiments by exposing it to prey suspended from nylon threads in the air and to food placed onto the water surface at varying distances to clutter-producing background (water plants). The bat revealed flexibility in foraging mode and caught prey in the air (aerial hawking) and from the water surface (trawling). M. macrophyllum was constrained in finding food very near to and within clutter. As echolocation was the prime sensory mode used by M. macrophyllum for detection and localization of food, the bat might have been unable to perceive sufficient information from prey near clutter as background echoes from the water plant increasingly overlapped with echoes from food. The importance of echolocation for foraging is reflected in a stereotypic call pattern of M. macrophyllum that resembles other aerial insectivorous and trawling bats with a pronounced terminal phase (buzz) prior to capture attempts. Our findings contrast studies of other phyllostomid bats that glean prey very near or from vegetation, often using additional sensory cues, such as prey-produced noise, to find food and that lack a terminal phase in echolocation behavior. In M. macrophyllum, acoustic characteristics of its foraging habitat have shaped its sonar system more than phylogeny.